PENERAPAN SANKSI PIDANA KEPADA PELAKU VIDEO CALL SEX (VCS) DITINJAU DARI PERUNDANG- UNDANGAN DI INDONESIA - Adela Isadora Artanta; Lonna Yohanes Lengkong; Inri Januar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
The main issue of Video Call Sex in this research is regarding legal protection and legal certainty related to the enforcement of criminal sanctions against VCS perpetrators. The type of research used in this writing is normative jurisprudence with a statute approach, as well as using secondary data of primary, secondary, and tertiary legal materials. The research uses approaches from primary legal materials such as the Criminal Law Book, Law Number 1 of 2023, Law Number 44 of 2008 on Pornography, Law No. 11 of 2008 about Electronic Information and Transactions, Act No. 32 of 2002 on Broadcasting, Act Number 23 of 2002 about Child Protection, Secondary and Tertiary Legal Materials. Even though VCS are in the pornographic realm, it is said that the perpetrator was the person who distributed VCS. Then, criminal sanctions against the buyer in the context of selling this service can be attributed under Article 4 of the Pornography Act along with Article 55 of the Code.